Principles for Settlement of Manufacturing Business Contract Disputes - Iswantoro; I Made Kanthika; Markoni; Zulfikar Judge (GoAcademica Research & Publishing, 2023)
Manufacturing business contract is agreements that are unique in the procurement of goods and services. Execution of these business contracts often encounters obstacles because there are errors in interpreting contract clauses that can lead to a settlement. After a dispute occurs, what efforts can be made by the parties in resolving disturbances that occur in the procurement of goods, and what is the settlement process if there is a discrepancy in the delivery of goods that are in accordance with the contract but are claimed not to meet the technical specifications stated in the business contract? The purpose of this research is to analyze the manufacturing business contract between Gagah Lambang Perkasa (GLP) and PT Corin Teknik Solusi (CTS). This study used a normative juridical method by reviewing and examining the contents of the agreement. The results show that CTS's failure to interpret the contents of the contract occurred because of the inaccuracy of the technical data on the ordered goods provided by GLP. The efforts made by GLP and CTS to resolve the disputes were by negotiation that prioritized good faith to reach a mutually beneficial agreement. The dispute resolution was achieved with CTS's willingness to accept GLP's claims. GLP provides compensation in the form of additional time, cost, and new orders for CTS so that the agreement can be implemented properly and business relations still run well. The conclusion obtained from this research is that the principle of resolving disputes in invoice business contracts is a mutual benefit (win-win solution) so that the business contract can be continued and not hamper the production process.